2019
DOI: 10.5897/ajar2018.13568
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and adaptation strategies to drought and erratic rains as key extreme events: Insights from small scale farming households in mixed crop agro ecosystems of semi-arid eastern Kenya

Abstract: Climate variability and change are some of the most pressing environmental challenges in semi-arid Kenya and Sub Saharan Africa (SSA) and are associated with persistent droughts, dry spells and erratic rains. The present study aimed at determining exposure and adaptation mechanisms among selected small-scale farmers cultivating drought tolerant crops in Wote, Makueni County, Eastern Kenya in the period 2003 to 2013. The sampled 120 farmers cultivate sorghum, cow peas and pigeon peas, which are some of the domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Mululam and Melak [22] reported that 69% of farmers in North-Western Ethiopia used finger millet straw for animal feed, while 12% used the straw as a construction material. Studies in China showed that the replacement of other straws like corn straw with finger millet straw improved the growth of sheep and was recommended in fattened lamb production [57].…”
Section: Various Uses Of Finger Milletmentioning
confidence: 99%
“…Mululam and Melak [22] reported that 69% of farmers in North-Western Ethiopia used finger millet straw for animal feed, while 12% used the straw as a construction material. Studies in China showed that the replacement of other straws like corn straw with finger millet straw improved the growth of sheep and was recommended in fattened lamb production [57].…”
Section: Various Uses Of Finger Milletmentioning
confidence: 99%
“…In Sub-Saharan Africa (SSA), rain-fed agriculture is the dominant source of food production practice by most smallholder farmers [1,2]. Droughts and dry spells are common in the tropics [3].…”
Section: Introductionmentioning
confidence: 99%